Genetic factors shaping the plasma lipidome and the relations to cardiometabolic risk in children and adolescentsResearch in context - Yun Huang; Sara Elizabeth Stinson; Malte Thodberg; Louise Aas Holm; Roman Thielemann; Karolina Sulek; Morten Asp Vonsild Lund; Cilius Esmann Fonvig; Min Kim; Kajetan Trost; Helene Bæk Juel; Trine Nielsen; et al. (EBioMedicine)
Summary: Background: Lipid species are emerging as biomarkers for cardiometabolic risk in both adults and children. The genetic regulation of lipid species and their impact on cardiometabolic risk during early life remain unexplored. Methods: Using mass spectrometry-based lipidomics, we measured 227 plasma lipid species in 1149 children and adolescents (44.8% boys) with a median age of 11.2 years. We performed genome-wide association analyses to identify genetic variants influencing lipid species. Colocalisation and Mendelian randomisation (MR) analyses were performed to infer causality between lipid species and cardiometabolic outcomes. Findings: We identified 37 genome-wide significant loci for 52 lipid species, nine of which are previously unreported. Colocalisation analyses revealed that seven lipid loci shared genetic variants associated with adult cardiometabolic outcomes. One-sample MR analysis identified positive causal associations between ceramides and liver enzymes, sphingomyelins and hemoglobin A1c (HbA1c), and phosphatidylethanolamines and high-sensitivity C-reactive protein in children and adolescents. Two-sample MR using adult-based summary statistics showed consistent direction of associations and indicated additional causal links, specifically between ceramides and elevated HbA1c levels, and phosphatidylinositols with elevated liver enzymes. Interpretation: These findings highlight the potential long-term implications of plasma lipid genetic determinants on cardiometabolic risk. Funding: Novo Nordisk Foundation, The Innovation Fund Denmark, The Danish Heart Foundation, EU Horizon, and LundbeckFonden.